The association of Malnutrition-Inflammation Score with sleep quality and mental health in hemodialysis patients: a multicenter cross-sectional study - Mehrnaz Morvaridi; Hossein Bavi Behbahani; Meysam Alipour; Ahmad Zare Javid; Sara Keramatzadeh; Shiva Shokri; Pardis Tofighzadeh; Fatemeh Fayazfar; Haleh Soltaniyan Dehkordi; Elahe Ghadimi; Siavash Babajafari Esfandabad; Shokouh Shayanpour (BMC Nephrology)
Abstract Background Hemodialysis is crucial for individuals with end-stage renal disease (ESRD), but it poses challenges that impact health and quality of life. Malnutrition, inflammation, sleep disturbances, and mental health disorders are common among hemodialysis patients, interconnecting and influencing outcomes. Therefore, the study aimed to investigate the association between the Malnutrition-Inflammation Score (MIS) and various health parameters, including sleep quality and mental health in hemodialysis patients. Methods A multicenter cross-sectional study investigated the association between the MIS and health parameters in 423 hemodialysis patients across eight centers. Assessments included MIS, physical activity levels, dietary intake, sleep quality, and mental health status, along with biochemical parameters. Statistical analyses using SPSS software were conducted to identify associations. Results Significant differences were observed in demographic, clinical, and biochemical characteristics across MIS quartiles (p < .05). Older age, lower BMI, longer dialysis vintage, and altered biochemical profiles were noted in higher MIS quartiles. Depression scores were significantly higher in higher MIS quartiles (p = .04). Multivariable analyses confirmed these associations, indicating higher odds of poorer sleep quality, depression, and anxiety with increasing MIS quartiles (p < .05). Conclusion The study highlights the intricate association between malnutrition, inflammation, sleep quality, and mental health conditions in hemodialysis patients. Addressing these factors comprehensively and tailoring interventions may lead to improved outcomes and well-being.